The Effects of Triethylene Glycol Dimethacrylate (TEGDMA) on the Protein of Human Dental Pulp Cells - Ratna Farida; Dewi Fatma; Karina Karina; Tanaya S. Tanaya; Pardamean RAS Pardamean (Faculty of Dentistry, Universitas Indonesia, 2013)
Triethylene glycol dimethacrylate (TEGDMA) is a common component of the bonding agents and resin composites used in dentistry for restorative dentistry. However, TEGDMA could be released from composite resins following incomplete polymerization and degradation processes by salivary enzyme in the mouth. Subsequently, TEGDMA is available in saliva and diffuses toward and affects the dental pulp which contains various cells, and thus may cause severe cytotoxic effects. Objectives: To determine the total protein concentration of human dental ulp cells following exposure to TEGDMA. Materials and Methods: Dental pulp cells were isolated from the pulp of the freshly extracted teeth and cultured in DMEM for 48 h (37ºC, 5% CO2). Then, 2 mM and 4 mM, and 8 mM TEGDMA were added to these cells and incubated for 24 h. The total protein was measured by Bradford Protein Assay. Results: The total protein concentration of dental pulp cells after exposure to 4 mM, 8mM, and 12 mM TEGDMA were statistically lower (22762.27 µg/ml ± 3385.87; 20268.44 µg/ml ± 1701.14; 23706.51 µg/ml ± 3214.52; respectively) than the control group (24253.77 µg/ml ± 3072.99). Furthermore, the total protein concentration of culture medium after exposure to 4 mM, 8 mM, and 2 mM TEGDMA, were statistically higher (28635.85 µg/ml ± 2373.4; 35288.41 µg/ml ± 3469.48; 38199.79 µg/ml ± 2752.47; respectively) when compared with the controls (27073.83 µg/ml ± 2772.47). Conclusion: 2 mM, 4 mM, and 8 mM TEGDMA caused cytotoxity to human dental pulp cells chowed by decreasing the total protein of cells and increasing the total protein of the culture medium. DOI: 10.14693/jdi.v16i3.102